Influence of Educational Engineering on remote meaningful learning of the Defined Integral - Diaz-Solano, Jimmi J. (2023)
This research was conducted during remote clases due to the pandemic generated by Covid-19, whose objective was to determine the level of influence that Didactic Engineering has on the Meaningful Learning of the Definite Integral in the students of the VII semester of the Faculty of Education of the Universidad Nacional del Centro del Perú, in 2021-I. The research has a quantitative approach, experimental, applicative level and quasi experimental design on a census sample of 26 students, from wich the control and experimental groups were formed randomly and prioritizig the equivalence of average, each with 13 students. Didactic Engineering was applied in the experimental group, through preliminary analysis and a priori analysis, so that the results were processed by Student’s t-test and p-value was p=0.000<0.05, so that the null hypothesis was rejected; while in the control group the same test generated the p-value equal to p=0.059>0.05, so that the null hypothesis was accepted with a confidence level of 95%. For that reason, these results allow us to conclude that Didactic Engineering has a high influence on the Meaningful Learning of the Definite Integral in the students of the VII semester of the Mathematical Sciences and Computer Science Carrer of the Faculty of Education of the Universidad Nacional del Centro del Perú.